Spinoza, the Gospel, and the Inversion of Christian Political Theology - Woszczek, Marek (Sensus Historiae, 2022)
The paper studies Spinoza’s remarks on Jesus and his pioneering exegesis of Gospels from Tractatus Theologico-Politicus in the context of modern research on the pre-gospel formation of Christology, early Christian sapiential traditions and the primitive Christian ethics as reconstructed from the Sayings Gospel Q. There is a long-standing controversy concerning the putative Enlightenment Christology of Spinoza, as well as his immanentist interpretation of the ‘regnum Dei,’ since he offered them only fragmentarily and in passing. In effect, his plain identification of Christ (‘Christus secundum spiritum’) with God’s Wisdom (‘sapientia Dei’ = ‘idea Dei’ = Sophia) and, allegedly, of the ‘Kingdom of God’ with that Wisdom’s presence in men’s actions also seem highly unusual, like modern invention and theological speculation, without any internal relation with ontology from his Ethics as well. I argue, to the contrary, that Spinoza’s sketchy, nonorthodox Christology is entirely consistent with the latter, and it also fully conforms to his general political ontology, reversed (immanentist) political theology and the unique ethico-political, naturalistic interpretation of ‘regnum Dei.’ I indicate that the ‘Christ-Sapientia’ coalescence places Spinoza in the primitive Christian sapiential tradition, which he could have discerned by closely studying the Gospel of Matthew and taking it as reflecting the original teaching of Jesus. It shows that the reversed Spinozian political theology closely resembles the radical non-messianic ethics of equality and social justice as represented in the formative stratum of the Sayings Gospel Q. In particular, I argue that the sapiential theology of entos hymōn from Q 17:21 and the cancellation of debts from Q 11:4 might even be read as part of the Spinozian theology of just economy. Paradoxically, Spinoza’s Enlightenment exegesis from Tractatus looks much more faithful to the primitive stratum of Christian political ethics than representations of the latter produced by modern anti-Enlightenment political theology. In fact, there seems to be unexpected proximity between that stratum and a purely immanentist liberation theology mentioned by Spinoza in the scholium to Prop. LXVIII in Book IV of Ethics.